Предмет: Алгебра,
автор: Аноним
у=х^2(х+3)
вычислите производную функцию
решите пожалуйста
Ответы
Автор ответа:
0
y=x^2(x+3)
(x^2)'(x+3)-x^2(x+3)=2x^2+6x-x^2=x^2+6x
можешь Х в конце за скобки вынести если хочешь, без разницы
(x^2)'(x+3)-x^2(x+3)=2x^2+6x-x^2=x^2+6x
можешь Х в конце за скобки вынести если хочешь, без разницы
Похожие вопросы
Предмет: Русский язык,
автор: markgortadze
Предмет: Литература,
автор: Аноним
Предмет: Математика,
автор: grigorysuper1
Предмет: Геометрия,
автор: Ка2388091
Предмет: Химия,
автор: qazxsw12987